Immunosuppressants alter the immune response associated with Glucantime® treatment for Leishmania infantum infection in a mouse model - Bernardo, Lorena; Solana, Jose Carlos; Sánchez, Carmen; Torres, Ana; Reyes-Cruz, Eder Yaveth; Carrillo, Eugenia; Moreno, Javier (Frontiers in Immunology, 2023)
Background: Immunosuppression is a major risk factor for the development of visceral leishmaniasis (VL). The number of patients receiving immunosuppressant drugs such as TNF antagonist (anti-TNF) and methotrexate (MTX) is increasing. In these patients, VL is more severe, their response to treatment poorer, and they are at higher risk of relapse, a consequence (largely) of the poor and inappropriate immune response they develop.Objectives: To examine the effect of immunosuppressive treatment on the host immune response and thus gain insight into the reduced efficacy of pentavalent antimonials in these patients. Experiments were performed using BALB/c mice immunosuppressed with anti-TNF or MTX, infected with Leishmania infantum promastigotes, and then treated with Glucantime ® at clinical doses.Results: Immunosuppression with both agents impeded parasite elimination from the spleen and bone marrow. Low pro-inflammatory cytokine production by CD4 + and CD8 + T cells was detected, along with an increase in PD-1 and IL-10 expression by B and T cells in the immunosuppressed groups after treatment. This is a provisional file, not the final typeset article Conclusions: The immunosuppressed mice were unable to develop specific cellular immunity to the parasite, perhaps explaining the greater risk of VL relapse seen in pharmacologically immunosuppressed human patients.